The Scent of Sleep: On Night Knowledge and Its Atmospheres - Huber, Sandra (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2023)
What does scent have to say concerning the wider networks involved in the lived experiences of sleep? In this essay, I discuss the connection of scent to sleepers and sleepers to scent, not only in the ways that scent may enter our dreams to change them up but also the ways that technologies and methodologies of air, perfume, breath, or exhaust connect us as sleepers to the worlds of botany, synthetics, and other realms of kinship and sense that exist apace from dominant modes of waking or seeing. If sleep and scent have historically been situated as “empty” and “passive,” this essay aims to show how full, vital, and roomy these spaces can be. In this line, I move scent and sleep through an atmospheric methodology of rooms to unravel their wider relationship to night knowledge, an epistemology that seeks alternatives to enlightened knowledges of the day, reaching into secrets and spirits. To do so, my archive involves theory, technology, perfume blogs, artists, dreamers, anthropologists, activists, poets, architects, and botanical, animal, and synthetic elements. Finally, I ask: if sleep had a scent, what would it be?